2020
DOI: 10.24843/eja.2020.v30.i11.p06
|View full text |Cite
|
Sign up to set email alerts
|

Whistleblowing System, Competence, Morality, and Internal Control System Against Fraud Prevention on Village Financial Management in Denpasar

Abstract: This study aims to test empirically the effect of the whistleblowing system, human resource competence, morality and internal control systems on fraud prevention in village financial management. The data source used is primary data from the results of distributing questionnaires to village officials who are involved as managers of village fund allocations as many as 97 respondents.  The sampling technique was the total method or census, namely 27 Dinas Villages in Denpasar City and data analysis used multiple … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
15
2
19

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(41 citation statements)
references
References 0 publications
5
15
2
19
Order By: Relevance
“…This is also indicated by the respondent's statement stating that the availability of a complaint system and reporting of complaints for internal fraud of the village government can prevent fraud in village funds. The results of this study are not in line with the research of Sujana et al, (2020) showed that the whistleblowing system has no effect on Fraud Prevention, but the results of this study strengthen the results of research Agusyani et al, (2016), and Romadaniati et al, (2020) showed that whistleblowing system affects fraud prevention.…”
Section: Whistleblowing System and Fraud Preventioncontrasting
confidence: 87%
See 1 more Smart Citation
“…This is also indicated by the respondent's statement stating that the availability of a complaint system and reporting of complaints for internal fraud of the village government can prevent fraud in village funds. The results of this study are not in line with the research of Sujana et al, (2020) showed that the whistleblowing system has no effect on Fraud Prevention, but the results of this study strengthen the results of research Agusyani et al, (2016), and Romadaniati et al, (2020) showed that whistleblowing system affects fraud prevention.…”
Section: Whistleblowing System and Fraud Preventioncontrasting
confidence: 87%
“…According to Larasati et al, (2017) whistleblowing system is a form of complaint about fraud involving certain persons inside the entity or outside the entity who take advantage personally within the entity. Agusyani et al, (2016) showed that the whistleblowing system affects Fraud Prevention, but Research of Sujana et al, (2020) showed that the Whistleblowing system does not affect fraud prevention. However, Romadaniati et al, (2020) show that the whistleblowing system affects fraud prevention.…”
Section: Introductionmentioning
confidence: 99%
“…Community participation is the involvement of the community's participation in government activities on evaluating and controlling government performance and minimizing abuse of authority. Sujana et al (2020); Wijayanti & Hanafi (2018); Atmadja & Saputra (2017); Taufik (2019), found the implementation of effective internal control will reduce the tendency of fraud in the village government, but Wonar et al (2018); Rahayu et al (2019); Lari Dashtbayaz et al (2019); Usman et al (2015), found contrary results. The results of research on community participation contribute to prevention of frauds were obtained by Mahayani (2017); Atiningsih (2019), which stated that community participation has significantly and positively affected towards prevention of frauds, however Yanto & Aqfir (2020); Ermawati (2017); Nafsiah & Diana (2020), found contrary results, The inconsistency of the results of previous studies regarding the effectiveness of internal control and community participation on fraud prevention is thought to be due to other factors that influence the relationship between variables.…”
Section: Organizational Culture As Moderating the Influence Of Internal Control And Community Participation On Fraud Prevention In Villagmentioning
confidence: 99%
“…Theory Fraud Triangle also explained that if internal controls are weak, it can be an opportunity to conduct fraud. Effective internal control can provide a guarantee that there will be no fraud [19], and so that internal control can function properly, it must evaluate all applicable systems and procedures [20] and so that the effectiveness of internal control runs well, the monitoring, information and communication processes, risk assessment, and control environment must be ensured to be well-coordinated [21]. Good internal control automatically detects and allocates errors so that fraud does not occur.…”
Section: Literature Reviewmentioning
confidence: 99%